Experimental study on the effective thermal conductivity of methane hydrate-bearing sand - Li, Dongliang; Liang, Deqing (International Journal of Heat and Mass Transfer, 2016)
The thermal conductivities of methane hydrate-bearing sand samples, formed from moist sand with different initial water saturation levels, were measured by Gustafsson's transient plane source (TPS) technique. The thermal conductivity values show weak negative dependence on temperature similar to a crystal-like material, which agrees well with most of the published results on sedimentary and pure methane hydrates. Similar dependence has also been observed in the wave speed studies. The effective thermal conductivity of hydrate-bearing sediment is strongly dependent on the morphology of the sediment. In partially water-saturated, gas-rich environments, the hydrates tend to cement sediment grains together, and even a small amount of hydrates presence can significantly increase the effective thermal conductivity of the sediments. In sand samples with high water concentrations and water-saturated sand, the effective thermal conductivity does not show an obvious increase with the hydrate saturation level. (C) 2015 Elsevier Ltd. All rights reserved.